Front Cover: Insights into the Scholl Coupling Reaction: A Key Transformation of Relevance to the Synthesis of Graphenes and Related Systems (Eur. J. Org. Chem. 13/2017). Issue 13 (28th March 2017) - Little, Mark S.; Yeates, Stephen G.; Alwattar, Aula A.; Heard, Kane W. J.; Raftery, James; Edwards, Alyn C.; Parry, Adam. V. S.; Quayle, Peter
Abstract : The cover picture shows the structures that are obtained from the Scholl‐type dehydrogenative coupling of 4, 10‐di‐substituted chrysene derivatives using 2, 3‐dichloro‐5, 6‐dicyano‐1, 4‐benzoquinone (DDQ) in the presence of trifluoroacetic acid. The unexpected outcomes of these reactions (including hydroxylative dimerisation) are supported by single‐crystal X‐ray structure determinations and probed by DFT calculations. A mechanistic rational, which involves the generation of radical‐cation intermediates, is presented in order to explain the varied nature of the products. Details are discussed in the Full Paper by M. S. Little, S. G. Yeates, P. Quayle et al. on page 1694 ff (DOI:10.1002/ejoc.201601580 ).